A stepped wedge trial of efficacy and scalability of a virtual clinical pharmacy service (VCPS) in rural and remote NSW health facilities - Julaine Allan; Shannon Nott; Brett Chambers; Ged Hawthorn; Alice Munro; Chris Doran; Chris Oldmeadow; Clare Coleman; Teesta Saksena (BMC, 2020)
Abstract Background Medication errors are a leading cause of mortality and morbidity. Clinical pharmacy services provided in hospital can reduce medication errors and medication related harm. However, few rural or remote hospitals in Australia have a clinical pharmacy service. This study will evaluate a virtual clinical pharmacy service (VCPS) provided via telehealth to eight rural and remote hospitals in NSW, Australia. Methods A stepped wedge cluster randomised trial design will use routinely collected data from patients' electronic medical records (n = 2080) to evaluate the VCPS at eight facilities. The sequence of steps is randomised, allowing for control of potential confounding temporal trends. Primary outcomes are number of medication reconciliations completed on admission and discharge. Secondary outcomes are length of stay, falls and 28 day readmissions. A cost-effectiveness analysis (CEA) and cost-benefit analysis (CBA) will be conducted. The CEA will answer the question of whether the VCPS is more cost-effective compared to treatment as usual; the CBA will consider the rate of return on investing in the VCPS. A patient experience measure (n = 500) and medication adherence questionnaire (n = 100 pre and post) will also be used to identify patient responses to the virtual service. Focus groups will investigate implementation from hospital staff perspectives at each site. Analyses of routine data will comprise generalised linear mixed models. Descriptive statistical analysis will summarise patient experience responses. Differences in medication adherence will be compared using linear regression models. Thematic analysis of focus groups will identify barriers and facilitators to VCPS implementation. Discussion We aim to demonstrate the effectiveness of virtual pharmacy interventions for rural populations, and inform best practice for using virtual healthcare to improve access to pharmacy services. It is widely recognised that clinical pharmacists are best placed to reduce medication errors. However, pharmacy services are limited in rural and remote hospitals. This project will provide evidence about ways in which the benefits of hospital pharmacists can be maximised utilising telehealth technology. If successful, this project can provide a model for pharmacy delivery in rural and remote locations. Trial registration Australian New Zealand Clinical Trials Registry (ANZCTR) -ACTRN12619001757101 Prospectively registered on 11 December 2019. Record available from: https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=378878&isReview=true